SOME CONSIDERATIONS REGARDING THE PRIMARY WHEAT SUPPLY IN ROMANIA AND ITS COMPOSITION (2014 – 2016) - Dragoș Mihai MEDELETE; Radu Lucian PÂNZARU; Marius VLADU; Gheorghe MATEI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study seeks to establish an anchoring, in time, of the Romanian primary wheat supply, having regard to the importance of the respective product for the Romanian agricultural economy (the second crop plant at national level based on cultivated areas and total yields). In the same context, the importance of wheat crop can be revealed through the role that this product can play as an export item - especially in years characterized by considerable levels of yields. In the period 2014-2016, the levels of the cultivated area and the total production (2,119,062.67 ha and 7,992,788.67 t) are highlighted, but also the less appropriate performance in terms of average production (3,771 kg/ ha). It is worth mentioning that certain aspects that influence the preforms of the respective culture need to be improved: the stronger atomicity of producers, the financing measures (non-reimbursable EU funds not accessible to the large mass of producers), the adequate upgrading of capital items mechanical capital and the upgrading of storage and preservation areas), the protection of certain categories of producers from the sensitive aspects of the market (for example, the evolution of the marketing prices).